Pengaruh Disiplin Kerja dan Punishment Terhadap Kinerja Pegawai pada PT. Industri Karet Deli Bagian Seksi RIB - Wahyu Syahputra; Nahar Maganda Saragih (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Employee performance is a description of the level of achievement of the implementation of an activity program or policy to realize the goals, objectives, vision and mission of an organization as outlined in a strategic plan. Punishment or punishment is a form of procedure or action given to individuals or groups for mistakes, violations or crimes that are made in the form of negative reinforcement or suffering in the context of fostering and improving behavior so that it does not happen again. This study aims to determine the effect of work discipline partially on employee performance at PT. Deli Rubber Industry especially in the R1B section. The method in this study used a quantitative approach and the number of samples taken in this study were 104 respondents, the data collection technique in this study used a questionnaire. Data analysis used multiple linear regression tests with the SPSS 25 program, so that research shows that work discipline partially affects employee performance.